Investigation of phytochemical composition and metabolite profiling in vivo of Beta vulgaris L. (19th August 2021) - Zhang, Xiaoyong; Chen, Xuezhao; Li, Wei; Zhu, Wei; Ge, Zhiwei; Gong, Minghua; Li, Shouxin; Tian, Jingkui
Abstract : Rationale: Beta vulgaris L. has attracted increasing attention because of its broad application. The root of B. vulgaris L. (beetroot) possesses many excellent biological properties such as antianemic, anti‐inflammatory, antihypertensive, antioxidant, anticarcinogenic, antipyretic, antibacterial, detoxicant, and diuretic. The chemical constituents of beetroot play a major role in the research on beetroot application and development. At present, no systematic identification study that focuses on the chemical constituents of beetroot has been reported. Methods: This study investigated a three‐step strategy comprising phytochemical profiling, prototype profiling, and metabolism of its correlative metabolites in vivo using ultra‐performance liquid chromatography tandem quadruple time‐of‐flight mass spectrometry (UPLC‐QTOF‐MS/MS). Results: UPLC‐QTOF‐MS/MS technique proved to be a rapid, sensitive, and reliable method for monitoring the specific ingredients as well as the whole chemical constituents in beetroot. In sum, 95 phytochemical compounds, 51 prototype compounds, and 37 derived metabolites in vivo were found in beetroot. Conclusions: The main metabolic pathways were sulfonation, glucuronidation, methylation/sulfonation, and methylation. The present findings provided the phytochemical basis both in vitro and in vivo for future application.